Trading Volume Analysis and Price Before Share and After Stock Split and the implications to Liquidity Indonesian Capital Market : ( Study Empirical in Companies Listed on the IDX in 2022 – 2024) - Wahyu Anggraini; Anna Christin Silaban; Akhmad Arfan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Research on stock splits has been widely conducted in Indonesia and internationally, as stock splits are considered an important corporate action that can influence investor perception and stock performance. However, the motivations and consequences of stock splits remain diverse, ranging from efforts to increase stock liquidity, adjust market price ranges, attract new investors, or signal positive corporate prospects. This study aims to empirically reanalyze the effect of stock splits on trading volume and stock prices of companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Specifically, the research investigates whether significant differences exist between trading activities and stock price levels before and after the stock split event. The data used in this study are historical in nature, consisting of stock split announcements, daily trading volume, and stock price movements surrounding the event period. To test the hypotheses, this research employs both the paired-sample t-test and the Wilcoxon signed-rank test as statistical tools. These tests are appropriate because they allow for the comparison of two related samples, namely the stock performance indicators before and after the split. The selection between the two methods depends on the distribution of the data, where the paired t-test is used if the data is normally distributed, while the Wilcoxon test is applied if the normality assumption is not met. This study is categorized as moderate TKT (Technology Readiness Level 4–6) because it uses secondary historical data and focuses on empirical statistical analysis rather than experimental or simulation-based approaches. By examining stock split events within the specified period, this research contributes to the understanding of whether stock splits in Indonesia are primarily cosmetic in nature or if they generate real economic impacts on liquidity and stock valuation. The findings are expected to provide useful insights for investors, market analysts, and policymakers in assessing the relevance and effectiveness of stock splits as a corporate strategy.